THE AESTHETIC OF PITA MAHA PAINTING: SOURCES OF CREATION IN CONTEMPORARY ART - Krisna Prabu, A.A. Gede Bayu Paramarta (ISI Press Institut Seni Indonesia Surakarta, 2024)
The creator, born in Padangtegal, Ubud, has appreciated Pita Maha artwork. Pita Maha painting is a genre that emerged in 1936, characterized by the fusion of classical Balinese and Western painting styles. The creator believes that the aesthetics of Pita Maha painting can serve as a foundation for artistic creation. This study employs a qualitative methodology, utilizing data collection techniques such as observation, documentation, interviews, and supplemented with library resources. The gathered data undergoes two phases: analysis to identify the concept, followed by the creation phase. The outcome of the study is a painting titled